Language Variation in Minang Colloquial Language Spoken in Kabun region: Sociolinguistic Study on Millennial Citizens - Condra Antoni; Irham Irham; Gusna Ronsi (JURNAL ARBITRER, 2019)
Despite the endless discussion on standard and non-standard language, Minangkabau and its dialect have less attention from scholars to study. This paper, therefore, aims to elaborate and compare the variation of Minang colloquial language and Sijunjung dialect spoken in Kabun region. Sociolinguistic theory on language variation and contact were employed to reveal such differences. In terms of data collection, we make use of Buffalo Trophy" as the data source and transcribe some potential words that fit the criteria. Afterward, we ask Sijunjung speakers to respond to those words. This process is recorded in a way to get sufficient interpretation of the possible variation among speakers. This study revealed that Minang and Sijunjung have several prominent dissimilarities in terms of phonological aspects. The changes occur from alveolar /r/ to voiced velar fricative /gh/, from /r/-/w/, from /a/-/o/, and /a/- /aw/. The findings confirmed that Minang as a standard language has phonological variations in Sijunjung dialect. Some of them may carry out new meanings, but the rest may not.